2012
DOI: 10.1152/japplphysiol.00786.2012
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training induces skeletal muscle hypertrophy and age-dependent adaptations in myofiber function in young and older men

Abstract: To examine potential age-specific adaptations in skeletal muscle size and myofiber contractile physiology in response to aerobic exercise, seven young (YM; 20 ± 1 yr) and six older men (OM; 74 ± 3 yr) performed 12 wk of cycle ergometer training. Muscle biopsies were obtained from the vastus lateralis to determine size and contractile properties of isolated slow [myosin heavy chain (MHC) I] and fast (MHC IIa) myofibers, MHC composition, and muscle protein concentration. Aerobic capacity was higher (P < 0.05) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
148
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 50 publications
18
148
2
2
Order By: Relevance
“…This has previously been demonstrated by similar absolute increases in VO 2max in the old and young (Murias et al 2010). However, it must be acknowledged that such large improvements are not always evident, as another study (Harber et al 2012) revealed a smaller training response in the old compared to young. Yet it is important to recognize the training intensity in this study was considerably lower (60-80 % of heart rate reserve) than in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…This has previously been demonstrated by similar absolute increases in VO 2max in the old and young (Murias et al 2010). However, it must be acknowledged that such large improvements are not always evident, as another study (Harber et al 2012) revealed a smaller training response in the old compared to young. Yet it is important to recognize the training intensity in this study was considerably lower (60-80 % of heart rate reserve) than in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…The role of the other correspondingly different variables is less clear. The hypertrophic effects of aerobic training have been equivocal and somewhat controversial (Harber et al, 2012;Lundberg et al, 2013), but several studies have shown increased muscle mass and increased slow oxidative fibre size after aerobic exercise training in mammals, including humans (Schwartz et al, 1991;Schluter and Fitts, 1994;Trappe et al, 2006;Harber and Trappe, 2008;Harber et al, 2009Harber et al, , 2012Konopka et al, 2010;Lovell et al, 2010). However, although FCSA certainly contributes to force production, it is less clear how a larger FCSA might increase endurance.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Harber et al (2012) showed that quadriceps muscle volume significantly increased by 5-6% after 12 weeks of cycle training (3-4 days per week at 60-80% HR reserve) in both untrained or minimally-trained young and older men 37) . A study by Bell et al (2000), however, showed no muscle hypertrophy after 12 weeks of cycle training performed at progressively increasing intensity with sessions (initially at the ventilatory threshold up to 90% V ・ O2max) for 21-42 min per day, 3 days per week 31) .…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%